2020
DOI: 10.1016/j.biotechadv.2020.107549
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose micro-nano fibres for wound healing applications

Abstract: Bacterial cellulose (BC) is cellulose produced by a few limited species of bacteria in given conditions. BC has many remarkable properties such as its high mechanical properties, water uptake ability and biocompatibility which makes it a very desirable material to be used for wound healing. Inherently due to these important properties, the material is very resistant to easy processing and thus difficult to produce into useful entities. Additionally, being rate limited by the dependency on bacterial production,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 152 publications
(74 reference statements)
0
102
0
Order By: Relevance
“…BC has highly unique characteristics, such as strong water retention, slow water liberation, high crystallinity, excellent thermal and mechanical properties, an ultra-dispersed fiber network, multifunctionality, absence of toxicity, and the ability to mold into 3D structures [ 3 ]. These features make it a promising material for use in biomedicine as drug carrier systems, matrices for tissue engineering, wound dressing materials, vessel implants, artificial blood vessels, biological films, and biosensors [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. BC is highly biocompatible due to its structural similarity to components of the extracellular matrix (e.g., collagen), and it undergoes complex interactions with biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…BC has highly unique characteristics, such as strong water retention, slow water liberation, high crystallinity, excellent thermal and mechanical properties, an ultra-dispersed fiber network, multifunctionality, absence of toxicity, and the ability to mold into 3D structures [ 3 ]. These features make it a promising material for use in biomedicine as drug carrier systems, matrices for tissue engineering, wound dressing materials, vessel implants, artificial blood vessels, biological films, and biosensors [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. BC is highly biocompatible due to its structural similarity to components of the extracellular matrix (e.g., collagen), and it undergoes complex interactions with biological tissues.…”
Section: Introductionmentioning
confidence: 99%
“…To cater for this issue, researchers have studied a few methods that can be effective against prevention of biofilm protection. This includes immobilization of lysozyme and glycoside hydrolase in BC [ 23 , 24 ]. In this context, several studies suggested that integration of lysozyme may increase the size of the particles which may cause significant alteration in specific activity [ 25 ].…”
Section: Enzymes As a Protection Agent For Bacterial Cellulosementioning
confidence: 99%
“…Most BC studies are currently focused in the biomedical field, where the multifunctionality of this polymer has been shown mainly through the development of biomaterials as wound dressing, scaffold for tissue engineering and drug delivery [135] (Table 1).…”
Section: Biomedical Area 1331 Worldmentioning
confidence: 99%